Investigation of multilayer domains in large-scale CVD monolayer graphene by optical imaging*Project supported by the National Natural Science Foundation of China (Nos. 61422503, 61376104), the Open Research Funds of Key Laboratory of MEMS of Ministry of Education (SEU, China), and the Fundamental Research Funds for the Central Universities. (March 2017) - Yu, Yuanfang; Li, Zhenzhen; Wang, Wenhui; Guo, Xitao; Jiang, Jie; Nan, Haiyan; Ni, Zhenhua
Abstract: CVD graphene is a promising candidate for optoelectronic applications due to its high quality and high yield. However, multi-layer domains could inevitably form at the nucleation centers during the growth. Here, we propose an optical imaging technique to precisely identify the multilayer domains and also the ratio of their coverage in large-scale CVD monolayer graphene. We have also shown that the stacking disorder in twisted bilayer graphene as well as the impurities on the graphene surface could be distinguished by optical imaging. Finally, we investigated the effects of bilayer domains on the optical and electrical properties of CVD graphene, and found that the carrier mobility of CVD graphene is seriously limited by scattering from bilayer domains. Our results could be useful for guiding future optoelectronic applications of large-scale CVD graphene.